Lassa fever in pregnancy with a positive maternal and fetal outcome: A case report - Joseph Agboeze; Matthew Igwe Nwali; Ebenezer Nwakpakpa; Onwe Emeka Ogah; Robinson Onoh; Justus Eze; Chukwuemeka Ukaegbe; Nnennaya Ajayi; Uzodimma Ugochukwu Nnadozie; Maria-Lauretta Orji; Kingsley Chiedozie Ojide; Sunday Uche Unigwe; et al. (International Journal of Infectious Diseases, 2019)
Background: The signs and symptoms of Lassa fever are initially indistinguishable from other febrile illnesses common in the tropics and complications of pregnancy. Surviving Lassa fever during pregnancy is rare. Only few cases have been documented. The antiviral drug of choice is ribavirin. Case description: A 25-year-old multigravida farmer with fever who was initially thought to have malaria in pregnancy at 29 weeks gestation. Further changes in her clinical state and laboratory tests led to a confirmation of Lassa fever. The Liver enzymes were markedly deranged and the packed cell volume was 27%. She commenced on ribavirin and subsequently was delivered of a live male neonate who was RT PCR negative for Lassa fever virus. Her clinical state improved, repeat RT PCR on day 15 was negative and she made full recovery. Discussion: The case reported had similar clinical features of fever and abdominal pain and resulted in the initial diagnoses of Malaria in pregnancy. When she failed to respond to antimalarial and antibiotics treatments, a strong suspicion of viral hemorrhagic fever was made. At this time the patient was in advanced stage of the disease with bleeding from vagina and puncture sites. On the third day of admission she was delivered of a live male neonate who remained negative after 2 consecutive RT PCR tests for Lassa fever virus. Lassa fever carries a high risk of death to the fetus throughout pregnancy and to the mother in the third trimester. Mothers with Lassa fever improved rapidly after evacuation of the uterus by spontaneous abortion, or normal delivery. She was clinically stable following delivery. Her laboratory investigations were essentially normal. Throughout her management transmission based precautions were observed. None of the six close contacts developed symptoms after been followed up for 21 days. Conclusion: This report adds to the body of literature that individuals can survive Lassa fever during pregnancy with good maternal and fetal outcome. Keywords: Abakaliki, Lassa fever, Pregnancy